SOCIO-ENVIRONMENTAL ASPECTS OF DIGITALISATION IN SERBIAN AGRICULTURE: FARMERS’ PERCEPTIONS - Nataša KLJAJIĆ; Vesna PARAUŠIĆ; Jonel SUBIĆ (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The authors examine the opinions of agricultural producers in Serbia about the impact of digitalisation in agriculture on the socio-environmental dimension of agricultural sustainability and the overall development of the country. Empirical data were collected through a semi-structured questionnaire and an interview with 53 producers who apply some of digital solutions on their farms. The research was conducted during a six-month period in 2023 (April – October). Responses to most questions regarding the social dimension of sustainability indicate some polarisation of opinions, as well as certain doubt about the contribution of digitalisation to this sustainability dimension. A unique and positive attitude is noticeable only in the assessment of the contribution of digitalisation to the reduction of the engaged labour force in agriculture and to the possibilities for greater diversification of farmers’ activities into various non-agricultural sectors. On the other hand, the respondents’ answers clearly show their positive perception of the contribution of digitalisation in production to the ecological aspects of agriculture and to the overall improvement of the environment. The largest percentage of the surveyed farmers’ recommendations for greater implementation of digitalisation in agricultural practices refer to directing more funds to subsidies and other forms of financial support, as well as to educating producers about digitalisation.